2018
DOI: 10.1029/2017jg004329
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Thermal and Moisture Sensitivity of Soil Organic Carbon Decomposition on Manure Composition in an Inceptisol Under a 5‐Year‐Old Maize‐Wheat Cropping System

Abstract: Hydrothermal sensitivity of soil organic carbon decomposition in relation to global climatic changes is of great importance for C cycle in an agro‐ecosystem. To assess the sensitivities of SOC as affected by different organic sources and mineral fertilizer in Inceptisol, soil samples from a 5‐year‐old field experiment were collected from unfertilized control, 100% NPK, vermicompost, compost, and farmyard manure (FM) treated plots and analyzed for total organic C, labile C fractions and C mineralization kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Higher R 2 were found for recalcitrant and stable C fractions than labile ones in both sandy and clayey soils ( Table 1B ). Biswas et al (2018) , Lian et al (2018) , Fang et al (2016) and Nguyen et al (2010) confirmed that recalcitrant and stable C fractions have higher responses to temperature than the labile C fractions in coarse and fine textured soils.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Higher R 2 were found for recalcitrant and stable C fractions than labile ones in both sandy and clayey soils ( Table 1B ). Biswas et al (2018) , Lian et al (2018) , Fang et al (2016) and Nguyen et al (2010) confirmed that recalcitrant and stable C fractions have higher responses to temperature than the labile C fractions in coarse and fine textured soils.…”
Section: Discussionmentioning
confidence: 75%
“…These C fractions are of utmost importance, owing to their direct and strong role in soil structure, C cycling and production and fluxes of CO 2 ( Badgery et al, 2020 ; Zomer et al, 2017 ). The C fractions are extremely susceptible to abiotic variables, and multiple earlier studies have demonstrated that the future C balance of terrestrial ecosystems is highly dependent on the consequences of global warming ( Wang et al, 2016 ; Qi et al, 2016 ; Biswas et al, 2018 ). Qi et al (2016) observed a significant reduction in soil labile organic C fractions in response to warming, while Karhu et al (2010) reported a decline in stable organic carbon fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, nitrogen and carbon mineralization rates in the soils were similar on both sides of the island. These suggest that the southern and northern forests'soils harbor similar microbial communities, at least in functional terms (Biswas et al 2018). In the laboratory, mineralization rate measures may underestimate actual field rates-the absence of plant roots and their mutualistic symbionts and alterations to the soil's physical and chemical characteristics are some of the factors known to bias mineralization rate estimates under laboratory conditions.…”
Section: Discussionmentioning
confidence: 92%
“…It has been observed that both MBC and TOC are affected by soil temperature and moisture, with a positive correlation with soil moisture and a negative correlation with soil temperature (Almeida et al., 2009). This hydrothermal sensitivity of soil C decomposition is of great importance when predicting the correlation between land‐use change and global climate change (Biswas et al., 2018). It is believed that TOC could be a better predictor of microbial C than particulate organic C (Rudrappa et al., 2006), as the latter accounts for the organic C fraction that is quickly decomposable and constitutes a transient C reserve in soils (Souza et al., 2016).…”
Section: Discussionmentioning
confidence: 99%